PENGARUH MOTIVASI KERJA TERHADAP PRESTASI KERJA (STUDI KASUS PADA TIGA PERUSAHAAN MAKANAN DAN MINUMAN TERBUKA/TBK) DI JAWA TIMUR - Moeheriono Moeheriono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
The objectives of the research are to examine the effects of motivation (physiological needs, safety security needs, social needs, esteems needs, self-actualization needs) on performances in the food and beverage industry (Go Public companies). The data wese gathered through the administration of questionnaires as well as direct interview with a selected subjects.The result of the research at multiple linier regression analysis model discover that motivation of physiological needs (0,3457), safety security needs (0,3072), social needs (0,191), esteem needs (0,0173), self-actualization needs (0,0166) has a significant positive effect on performance. The result of Analysis Variance (ANOVA) method has insignificant effects on the food and beverage industry (Go Public companies) (2,005).Other additional findings are also reported and further discussed, while several recommendations for future research are developed.